Internal heat loads profiles for buildings' energy modelling: comparison of different standards. (February 2023) - Ferrari, Simone; Zagarella, Federica; Caputo, Paola; Bonomolo, Marina
Highlights: Building internal heat load profiles from 5 standards are assessed and compared. Heat load density profiles per each standard are calculated for floor archetypes. Provided heat load density profiles can be directly used by energy modelers. Heat load composition and contribution to thermal energy needs are assessed. The elaborations support the choice of most suitable profile for energy simulation. Abstract: In absence of real data on occupants and electric devices patterns, nominal values and schedules of internal heat loads given by existing related standards can be adopted for buildings energy modelling. Since different results can be obtained depending on the standard, the choice of the proper one, based only on given nominal values and schedules, could be not straightforward. As a novelty, this study reports a comparison among the energy implications of different building internal heat load profiles from current standards. To this aim, typical building floors representing common residential and office rooms composition were defined. Then, different days' profiles and peaks of the overall internal heat loads densities due to occupancy, equipment, and artificial lighting, obtained from selected standards, are analyzed and compared together with the resulting different annual internal heat load density components and their effect on building annual thermal energy needs. Hence, insights to choose the most suitable standard, depending on the study context, are provided. Moreover, the calculated values of internal heat loads densities can be directly adopted as an early-stage approach in energy simulation models, neglecting detailing the building rooms' composition.